Invalidity of the Election - Chochova Мaria (Yearbook of the Law Department, 2020)
The statement addresses issues concerning the election as a basis for employment and the general rules of invalidity established in the Labor Code. Separate hypotheses are considered, in the presence of which there will be grounds for declaring the election invalid. A comparative analysis has been made between the proceedings challenging the legality of the election and challenging its validity.